Breast Milk Cytokines and Early Growth in Gambian Infants - Saso, Anja; Blyuss, Oleg; Munblit, Daniel; Faal, Amadou; Moore, Sophie E.; Le Doare, Kirsty (Frontiers in Pediatrics, 2019)
Background: Breast milk provides nutrition for infants but also delivers other bioactive factors that have key protective and developmental benefits. In particular, cytokines are thought to play a role in immunomodulation, although little is known about their impact on health outcomes in early life. Objective: The purpose of this pilot study was to evaluate the relationship between cytokines in breast milk and infant growth outcomes in a low-income setting. Methods: 100 mother-infant pairs were followed up to 2-3 months postpartum as part of a prospective longitudinal cohort study in urban Gambia, West Africa. The concentrations of 9 pro-inflammatory cytokines (IL-1β, IL-2, IL-4, IL-6, IL-10, IL-12, IL-13, IFN-γ, TNFα), IGF-1 and TGFβ2 were measured in colostrum within 12 hours of birth and in breast milk at the final visit, scheduled between day 60-89 postpartum. Infant weight was recorded and converted to weight-for-age Z-scores (WAZ) at the same time points. Growth outcomes were defined in our study as a) change in WAZ between birth and final visit b) WAZ at final visit. Linear regression analysis was used to determine the ability of colostrum and breast milk cytokine concentrations to predict growth outcomes up to 2-3 months postpartum. Results: Gambian infants demonstrated growth faltering across the first 2-3 months postpartum. There was no significant relationship between cytokines in colostrum and subsequent change in WAZ between birth and the final visit, in either unadjusted or adjusted models. However, cytokines in mature breast milk, TNFα, IFNγ, IL1β, IL2, IL4 and IL6, were weak negative predictors of WAZ scores at the final visit, in unadjusted models (p<0.05). When adjusted for maternal anemia (as a proxy for maternal nutrition), TNFα and IL6 remained significant predictors (p<0.05). Conclusions: Variations in breast milk cytokine levels do not play a substantial role in the growth faltering observed across early infancy. The potential contribution of other factors, such as micronutrients, hormones or human milk oligosaccharides, must be elucidated. Cytokine levels in mature breast milk were weakly predictive of poor infant growth, possibly reflecting a ‘read-out’ of suboptimal maternal health and nutrition.